Potential sperm contributions to the murine zygote predicted by in silico analysis. Issue 6 (December 2017) - Ntostis, Panagiotis; Carter, Deborah; Iles, David; Huntriss, John; Tzetis, Maria; Miller, David
Abstract : Paternal contributions to the zygote are thought to extend beyond delivery of the genome and paternal RNAs have been linked to epigenetic transgenerational inheritance in different species. In addition, sperm–egg fusion activates several downstream processes that contribute to zygote formation, including PLC zeta-mediated egg activation and maternal RNA clearance. Since a third of the preimplantation developmental period in the mouse occurs prior to the first cleavage stage, there is ample time for paternal RNAs or their encoded proteins potentially to interact and participate in early zygotic activities. To investigate this possibility, a bespoke next-generation RNA sequencing pipeline was employed for the first time to characterise and compare transcripts obtained from isolated murine sperm, MII eggs and pre-cleavage stage zygotes. Gene network analysis was then employed to identify potential interactions between paternally and maternally derived factors during the murine egg-to-zygote transition involving RNA clearance, protein clearance and post-transcriptional regulation of gene expression. Our in silico approach looked for factors in sperm, eggs and zygotes that could potentially interact co-operatively and synergistically during zygote formation. At least five sperm RNAs ( Hdac11, Fbxo2, Map1lc3a, Pcbp4 and Zfp821 ) met these requirements for a paternal contribution, which with complementary maternal co-factors suggest a wider potential for extra-genomic paternal involvement in the developing zygote.